Drivers of Academic Research and Patenting in India: Econometric Estimation of the Research Production Function - Amit Shovon Ray; Sabyasachi Saha (Indian Council for Research on International Economic Relations (ICRIER), 2010)
In this paper we attempt to provide a comprehensive understanding of the drivers of academic research and patenting in India. Academic research is conceptualised as a research production process where research inputs (like research time and number of research scholars) are transformed into research outputs in the form of publications and patents. We expect research inputs by a faculty member to be an outcome of his/her own decision-making process, which in turn determine his/her research outputs. Exogenous parameters, like faculty background, faculty attitude, research sponsorship and institutional factors, are expected to influence both set of endogenous variables (research inputs and outputs). We specify this production function as a recursive simultaneous equation model and estimate the structural parameters using standard econometric methods. Our results clearly identify several drivers of academic research and patenting in India, in terms of faculty background, faculty attitude and other parameters, from which we arrive at concrete policy lessons for patenting of academic research in India. In particular, we argue that putting in place institutional structures will not serve the purpose without addressing the fundamental issues of research environment, culture and attitude in the first place. In a sense, therefore, introducing an IPR legislation alone may not act as an instant magic formula to energise Indian academic research for commercial application.
Keywords: O31; O34; O38; I23; C51; 330; Academic reaesrch; patents; Bayh-Dole act; India; Universitäre Forschung; Patent; Technologiepolitik; Patentrecht; Produktionsfunktion; Schätzung; Indien